2014
DOI: 10.5423/ppj.oa.08.2014.0075
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Genetic Similarity of Vegetative Compatibility Groupings in Sclerotinia homoeocarpa

Abstract: Vegetative compatibility groups (VCGs) are determined for many fungi to test for the ability of fungal isolates to undergo heterokaryon formation. In several fungal plant pathogens, isolates belonging to a VCG have been shown to share significantly higher genetic similarity than those of different VCGs. In this study we sought to examine the relationship between VCG and genetic similarity of an important cool season turfgrass pathogen, Sclerotinia homoeocarpa. Twenty-two S. homoeocarpa isolates from the Midwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Simple sequence repeats (SSR) are effective at differentiating genotypes of A. flavus (Grubisha and Cotty, 2015; Picot et al ., 2018; Senghor et al ., 2020). Fungal VCGs frequently contain multiple closely related SSR haplotypes (Berbegal et al ., 2010; Chang et al ., 2014). SSR markers are valuable tools for genotyping A. flavus from agricultural (Tran‐Dinh et al ., 2009; Grubisha and Cotty, 2010, 2015; Sweany et al ., 2011; Ortega‐Beltran et al ., 2020) and clinical settings (Hadrich et al ., 2010; Dehghan et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Simple sequence repeats (SSR) are effective at differentiating genotypes of A. flavus (Grubisha and Cotty, 2015; Picot et al ., 2018; Senghor et al ., 2020). Fungal VCGs frequently contain multiple closely related SSR haplotypes (Berbegal et al ., 2010; Chang et al ., 2014). SSR markers are valuable tools for genotyping A. flavus from agricultural (Tran‐Dinh et al ., 2009; Grubisha and Cotty, 2010, 2015; Sweany et al ., 2011; Ortega‐Beltran et al ., 2020) and clinical settings (Hadrich et al ., 2010; Dehghan et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mycelial compatibility in S. sclerotiorum is considered by some to be synonymous with vegetative compatibility (Kohn et al 1990;Schafer and Kohn 2006), yet evidence to the contrary exists in S. sclerotiorum (Ford et al 1995), S. homoeocarpa (Jo et al 2008;Chang et al 2014), Verticillium dalhiae (Papaioannou and Typas 2014), and Neurospora crassa (Micali and Smith 2003). The crux in these cases is that barrage formation may only serve as indirect evidence for vegetative incompatibility.…”
Section: Mycelial Compatibility Is Not Vegetative Compatibilitymentioning
confidence: 99%
“…One explanation for the lack of congruence between MCG and VCG is that MCG represent subsets of VCG, such that one MCG may represent more than one VCG. While there is evidence that MCG are nested within VCG in S. homoeocarpa (Chang et al 2014), the relationship between mycelial compatibility and vegetative compatibility in S. sclerotiorum is more complex, as shown in Table 4 of Ford et al (1995), where one MCG was represented by two VCG and, in turn, both of these VCG represented two MCG. Microscopically, however, it was shown that the hyphae remained in a stable, heterokaryotic state, as evidenced by 4,6-diamidino-2-phenylindole (DAPI) staining and stable transfers of colonies.…”
Section: Mycelial Compatibility Is Not Vegetative Compatibilitymentioning
confidence: 99%
“…Mycelial compatibility in S. sclerotiorum is considered by some to be synonymous with vegetative compatibility (Kohn et al 1990;Schafer and Kohn 2006), yet evidence to the contrary exists in S. sclerotiorum (Ford et al 1995), S. homoeocarpa (Jo et al 2008;Chang et al 2014), Verticillium dalhiae (Papaioannou and Typas 2014), and Neurospora crassa (Micali and Smith 2003). The crux in these cases is that barrage formation may only serve as indirect evidence for vegetative incompatibility.…”
Section: Mycelial Compatibility Is Not Vegetative Compatibilitymentioning
confidence: 99%
“…One explanation for the lack of congruence between MCG and VCG is that MCG represent subsets of VCG, such that one MCG may represent more than one VCG. While there is evidence that MCG are nested within VCG in S. homoeocarpa (Chang et al 2014), the relationship between mycelial compatibility and vegetative compatibility in S. sclerotiorum is more complex, as shown in Table 4 of Ford et al (1995)…”
Section: Mycelial Compatibility Is Not Vegetative Compatibilitymentioning
confidence: 99%